CFD simulation of fixed bed dryer by using porous media concepts: Unpeeled longan case - Prukwarun, Wuttichai; Khumchoo, Wasan; Seancotr, Waraporn; Phupaichitkun, Sarawut (International Journal of Agricultural and Biological Engineering, 2013)
Quality of dried product depends on the temperature and velocity at each position in the dryer. Simultaneous microscopic and macroscopic simulation on Computational Fluid Dynamic (CFD) is a general problem of fixed bed dryer consisting of water transportation in porous media and dynamic flow of hot air in the dryer. Simplifying the dryer by assuming the packed bed as porous volume, viscous and inertial resistances (1/? and C2) are necessary for calculating the pressure drop and velocity change in the bulk. Comparing the ?P/L of the standard packing with experimental results, the porosity and resistance parameters can be estimated. Simulation of unmodified, adding false floor and invest mesh, and insulating the dryer wall are used for validation with previous results. Adding the round holed sieve as false floor and invert mesh can produce better profile but cannot obtain uniform distribution. Air velocity distribution shows similar but the calculating temperature is higher than that from the experiment. By analysis of thermal efficiency of dryer without insulator, the heat loss rates with flue gas and heat flux at wall are in the range 14%-17% and 5.5%-7.3%. Integrating with single fruit or thin layer drying kinetic in the future, the CFD simulation can be used for optimal design of fixed bed dryer.